Lipase “whole-cell” de Streptomyces clavuligerus : produção, caracterização e aplicação em meio orgânico - Santos, Jéssica Bravin Carmello dos (Universidade Federal de São Carlos, 2016)
Cell-associated lipases have been considered biocatalysts economically advantageous because they are produced at low cost, avoiding further recovery or purification steps. Few studies regarding Streptomyces clavuligerus lipase have reported the production of extracellular enzyme, although at first this had been considered a cell-associated enzyme. In this context, the aim of this work was the production of the cell-associated lipase from Streptomyces clavuligerus (whole-cell lipase, Sc-WCL) by submerged fermentation, the biochemical characterization of the enzyme and its use in the synthesis of butyl butyrate, an aroma ester with industrial importance. The culture conditions on rotary shaker and the operational parameters for cultivation in bioreactor were evaluated in order to establish a protocol for Sc- WCL production. The conditions for S. clavuligerus cultivation in rotary shaker that resulted in maximal hydrolytic activity of Sc-WCL (3,000 U.L-1) were: baffled flask, free-glycerol production medium, pH 6.8 and 28 °C. The operational parameters in bench reactor that resulted in maximal volumetric productivity of Sc-WCL (54 U.L-1.h-1) were agitation of 400 rpm and aeration of 1 vvm. The maximal volumetric productivity in bioreactor operated under selected conditions (52.5 U.L-1.h-1) was reached after 24 h, while similar productivity in rotary shaker (54.8 U.L-1.h -1) was achieved only after 48 h fermentation. The catalytic potential of Sc-WCL in hydrolysis reactions was comparable to the commercial lipase preparations. Sc- WCL was more active at 60 °C and pH 10.7, and stable at 30-40 °C after 1 h incubation at pH 10. For butyl butyrate synthesis catalyzed by Sc-WCL, the reaction conditions that resulted in higher ester conversion (85%) were: 5 g of Sc-WCL/ L, molar ratio of fatty acid: alcohol 1:1 in heptane and 8 h reaction. The stability at alkaline pH and organic medium (leastwise in heptane and butanol), associated with the low cost, make Sc-WCL attractive in industrial applications, such as flavors synthesis, detergent formulations, hydrolysis of vegetable oils, among others.
Keywords: Lipase “whole-cell”; Streptomyces clavuligerus; Fermentação submersa; Biorreator; Hidrólise; Whole-cell lipase; Submerged fermentation; Hydrolysis; Esterification; Butyl butyrate; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA